Multiple cities, Canada: Social Inclusion Audit and Toolkit for Local Libraries - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2010)
This is a case study of the Canadian Social Inclusion Audit and Toolkit for Local Libraries.
Keywords: Libraries; Social Inclusion